2016
DOI: 10.1007/s00709-016-0983-x
|View full text |Cite
|
Sign up to set email alerts
|

Different functions of the histone acetyltransferase HAC1 gene traced in the model species Medicago truncatula, Lotus japonicus and Arabidopsis thaliana

Abstract: In eukaryotes, histone acetyltransferases regulate the acetylation of histones and transcription factors, affecting chromatin structural organization, transcriptional regulation, and gene activation. To assess the role of HAC1, a gene encoding for a histone acetyltransferase in Medicago truncatula, stable transgenic lines with modified HAC1 expression in the model plants M. truncatula, Lotus japonicus, and Arabidopsis thaliana were generated by Agrobacterium-mediated transformation and used for functional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…So the different expression of BnaC08g41780D between zws-ms and zws-217 may result some unknown process in fruit development. (3) The knockdown of HAC1 causes disturbances in flower morphology in the Arabidopsis , such as a modified petal shape or even absence of petals [42]. HAC12 has high identity with HAC1 , but what morphology changes it can make are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…So the different expression of BnaC08g41780D between zws-ms and zws-217 may result some unknown process in fruit development. (3) The knockdown of HAC1 causes disturbances in flower morphology in the Arabidopsis , such as a modified petal shape or even absence of petals [42]. HAC12 has high identity with HAC1 , but what morphology changes it can make are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium-mediated transformation is ecotype dependent in many plants, as ecotypes respond differently with varying transformation efficiencies (transgenic plants/initial calli formed) [1316]. The A17 ecotype of M. truncatula serves as the reference accession for the genome [17] and although used widely in labs, it is considered difficult to transform [18].…”
Section: Introductionmentioning
confidence: 99%
“…The ZZ domain is relatively small in size and recent work has shown its role in binding the N-terminus of H3, allowing histone acetylation as well as methylation [50]. The HAC1 gene which was reported by [29], corresponding to Medtr7g105680.1 (Mt4.01), although showing a low degree of similarity with AtHAC1 (Blast-P score 121, 41% query cover, 2 × 10 −28 E-value, 37.5% identity), was not revealed by our analysis because it does not harbor a PF08214 domain.…”
Section: Histone Modifier Gene Families In Medicago Truncatulamentioning
confidence: 99%
“…A recent functional analysis of the three HDTs by RNAi knock-down that is restricted to nodules demonstrated that they play a key role in primordium formation and nodule development, because both meristem size and cell colonization by bacteria was reduced [28]. Another functional report for the gene HAC1 in M. truncatula, obtained by RNAi downregulation and gene over-expression, showed a range of alterations in plant organ development, supporting a fundamental role for the gene [29]. The expression of the MtJMJC5 gene, a putative Arabidopsis JMJ30/JMJD5 ortholog, was characterized during the circadian rhythm and shown to be oscillating with alternative splicing occurring under cold induction; no functional analysis was provided [30].…”
Section: Introductionmentioning
confidence: 96%